PENGARUH TEKNIK AROMA TERAPI LAVENDER TERHADAP PENGURANGAN RASA NYERI PADA PERSALINAN KALA I DI BIDANG PRAKTEK MANDIRI PERAWATI - Vera Christina Hulu; Agusanna Dewi Silangit (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2021)
ABSTRACT Childbirth and birth of the fetus at a sufficiently mature age, longitudinal location and percentage of head followed by removal of the placenta, and the entire birth process ends in less than 24 hours. But in the process it causes pain in the lower back at the beginning of labor to encircle the abdomen and when labor progresses it will produce greater pain. Pain arising is influenced by the central nervous system and brain. So that the administration of aromatherapy compounds through inhalation will directly have an effect on the central nervous system and relaxation in the brain. The results of a survey conducted in Independent Practice Midwives have never done lavender aromatherapy in reducing the level of pain. The aim was to determine the level of pain before and after administration of lavender aromatherapy. This type of research is quantitative analysis, quasi experimental research design, the population of all maternity mothers at the first time, with the technique of accidental sampling, the number of samples is 18 respondents, the data is processed using the Wilcoxon test. The results of the study of 18 respondents, the majority before being given lavender aromatherapy were the majority of the great pain scale as many as 10 mothers (55.6%) and the minor scale moderate pain scale as many as 8 mothers (44.4%). And after being given aromatherapy was the majority of moderate pain scale as many as 13 mothers (72.2%), and minor minor pain scale as many as 5 mothers (27.8%). With p_value 0.01